Análisis del biocomercio en Colombia para pymes como oportunidad en mercados internacionales - Salazar Quintero, Brayan Stiven (Universidad Antonio Nariño, 2022)
This research work seeks to expose the concept of "bio trade" as an opportunity for small and medium-sized enterprises (Pyres) in Colombia, making a review of those first world countries and making a comparative and competitive analysis of Colombia with Peru, a country that promotes such activities in Latin America